Perkembangan Akal Budi Manusia Pada Zaman Positifistik Dalam Perspektif Auguste Comte - Kadek Yuli Wahyu Astini; Putu Eka Arsadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Humans are the most dominant creatures, so humans have the largest population on earth at this time. There are so many works that have been owned by humans that have changed the way humans perceive the world. This is because humans are understood as intelligent creatures. It is with this intellect that man can manifest what he has thought into a reality which can become a truth. One of the philosophers who had this idea was Auguste Comte. He is one of the philosophers of the Positiveistic era with his thoughts on Positivism. Auguste Comte here further sharpens his thinking about that truth is obtained through Positivism. The positivism paradigm according to Auguste Comte shows that the resources for obtaining knowledge are by using reason and making observations. The use of reason is a human potential or way to achieve and express truth through observation until finding concepts, generalizations, legal propositions and theories. However, there are also some criticisms regarding Auguste Comte's positivism which are considered that Comte's thinking is entirely derivative. However, this response is actually wrong. Keywords: Intellect, Auguste Comte, and Positivism